Avaliação epidemilógica dos agravos à saúde dos trabalhadores da região de bauru no ano de 2003 - Otuka, Santina Tiemi Kusumi (2005)
It is about a descriptive epidemiology study of the work accidents occurred in Bauru and region, in the year of 2003. The work accidents are defined as the ones occurred during the working hours in the industry, or, the special insured people s work, causing corporal damage or functional perturbation, permanent or temporary, that causes death, or loss, or reduction of capacity to work. It is considered work accident the occupational disease and the work disease. It is compared to work accident: the accident connected to work which, although is not the only cause, has contributed directly the lesion occurrence; some accidents suffering by the insured person in the work place and during work hours; the disease proceeding from accidental contamination of the employee practicing his activity; the accident suffering at the service of the company or in the insured person s way between the residence and the work place or vice versa. It was accomplished an epidemiological study review published by several researchers, as well a review of the Brazilian Labour Legislation. The material used for this study were all the Work Accidents Communications (CATs), registered at the INSS agency in Bauru SP, in the year of 2003. The method was based in the study of the CATs in the descriptive form, where were analyzed the distribution, frequency and percentage of the work accidents, according to sex, age group, body part affected and the object that caused the lesion. The results showed that were registered 925 CATs in the year 2003, from these, 2 cases passed away. There was a bigger incidence of work accidents in masculine sex in respect to female sex. The most frequent work accidents were the typical ones, followed by occupational diseases and route ones. The body part most affected was the superior limb, followed by the inferior limb and thorax. In the distribution of the work accidents by age group predominated the 21 years old to 40 years old group, followed by the 41 years old to 60 years old group.